2002
DOI: 10.1063/1.1458030
|View full text |Cite
|
Sign up to set email alerts
|

Cylindrical and spherical dust ion–acoustic solitary waves

Abstract: The properties of cylindrical and spherical dust ion–acoustic solitary waves (DIASWs) in an unmagnetized dusty plasma, whose constituents are inertial ions, Boltzmann electrons, and stationary dust particles, are investigated by employing the reductive perturbation method. The modified Korteweg–de Vries equation is derived and its numerical solutions are obtained. It has been found that the properties of the DIASWs in a nonplanar cylindrical or spherical geometry differ from those in a planar one-dimensional g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
126
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 292 publications
(127 citation statements)
references
References 18 publications
1
126
0
Order By: Relevance
“…[11] have theoretically shown that due to the size effect on the secondary emission insulating dust grains in space plasmas can have the opposite polarity; large grains are negatively charged where as small one are positively charged; are found in different regions in space, like cometary tails [9,11,12], Jupiter's magmetosphere [13], etc. In Dust-ionacoustic (DIA) waves the restoring forces are provided by the thermal pressure of electrons and the inertia, which is due to the ion mass [14,15]. On the other hand, Cooney et al [16] presented an experimental observation of a two-dimensional soliton in plasmas which contains both positive and negative ions.…”
Section: Introductionmentioning
confidence: 99%
“…[11] have theoretically shown that due to the size effect on the secondary emission insulating dust grains in space plasmas can have the opposite polarity; large grains are negatively charged where as small one are positively charged; are found in different regions in space, like cometary tails [9,11,12], Jupiter's magmetosphere [13], etc. In Dust-ionacoustic (DIA) waves the restoring forces are provided by the thermal pressure of electrons and the inertia, which is due to the ion mass [14,15]. On the other hand, Cooney et al [16] presented an experimental observation of a two-dimensional soliton in plasmas which contains both positive and negative ions.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical prediction of Shukla and Silin [50] was supported by a number of laboratory experiments [52,60,61]. The nonlinear theory of DIA waves in different dusty plasma systems has been investigated by Bharuthram and Shukla [62] , Nakamura et al [63] , Luo et al [64] , Mamun and Shukla [65] , Shukla and Mamun [59] , Verheest et al [66] , Sayed and Mamun [67] , Alinejad [68], Baluku et al [69] , Das et al [70].…”
Section: Introductionmentioning
confidence: 96%
“…Therefore the modified KP equation containing a square root nonlinearity is very attractive model for the study of ion-acoustic waves in plasma and dusty plasma [34][35][36]. Extensive work has been devoted to the study of nonlinear waves associated with the dust ion-acoustic waves, particularly the dust ion-acoustic solitary and shock waves in dusty plasmas in which dust particles are stationary and provide only the neutrality [37]. The KP equation is derived [38] for the propagation of nonlinear waves in warm dusty plasmas with variable dust charge, two-temperature ions and nonthermal electrons by using the reductive perturbation theory.…”
Section: Schamel Equation and Modified Kp Equationmentioning
confidence: 99%